Zebrafish Heart Failure Models - Narumanchi, Suneeta; Wang, Hong; Perttunen, Sanni; Tikkanen, Ilkka; Lakkisto, Päivi; Paavola, Jere (Frontiers in Cell and Developmental Biology, 2021)
Heart failure causes significant morbidity and mortality worldwide. The understanding of heart failure pathomechanisms and options for treatment remain incomplete. Zebrafish has proven useful for modeling human heart diseases due to similarity of zebrafish and mammalian hearts, fast easily tractable development, and readily available genetic methods. Embryonic cardiac development is rapid and cardiac function is easy to observe and quantify. Reverse genetics, by using morpholinos and CRISPR-Cas9 to modulate gene function, make zebrafish a primary animal model for in vivo studies of candidate genes. Zebrafish are able to completely regenerate their hearts following injury. However, less attention has been given to using zebrafish models to increase understanding of heart failure and cardiac remodeling, including cardiac hypertrophy and hyperplasia. Here we discuss using zebrafish to study heart failure and cardiac remodeling, and review zebrafish genetic, drug-induced and other heart failure models, discussing the advantages and weaknesses of using zebrafish to model human heart disease. Using zebrafish models will lead to insights on the pathomechanisms of heart failure, with the aim to ultimately provide novel therapies for the prevention and treatment of heart failure.